Targeted therapies in pediatric B-Cell acute lymphoblastic leukemia: mechanisms, efficacy, and future directions - Correa-Carranza, Valeria; Rosario-Méndez, Guillermo; Castillejos-López, Manuel; Chávez-Pacheco, Juan Luis; Galván-Díaz, Cesar; Torres-Espíndola, Luz María (Frontiers in Pharmacology, 2026)
BackgroundAcute lymphoblastic leukemia (ALL) is the most common hematologic malignancy in children and is characterized by rapid progression and, in some cases, a high risk of relapse. Targeted therapies have revolutionized treatment with greater specificity, reduced systemic toxicity and a better prognosis.ObjectiveThis review provides a comprehensive analysis of current targeted therapies for pediatric B-cell ALL, focusing on their mechanisms of action, efficacy, safety profiles, advantages, and remaining challenges.MethodsA systematic review of clinical trials published over the past 15 years was conducted. The analyzed therapies include monoclonal antibodies, antibody‒drug conjugates, tyrosine kinase inhibitors, proteasome inhibitors, and chimeric antigen–receptor T-cell (CAR-T cell) immunotherapy.ResultsTargeted therapies improved progression-free survival and overall response rates, particularly in patients with relapsed/refractory ALL. CD19-directed CAR-T-cell therapy and bispecific antibodies (e.g., blinatumomab) have demonstrated high remission rates in early-phase clinical trials. Additionally, BCR-ABL1-positive ALL patients show benefit from tyrosine kinase inhibitors when combined with chemotherapy.ConclusionTargeted therapies represent a paradigm shift in ALL treatments, enabling more personalized and effective strategies. Their integration into standard protocols, especially for high-risk and relapsed patients, is crucial to enhancing long-term outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251110522, identifier CRD420251110522